Analyzing Role Overload, Mental Health, and Quality of Life Among Jordanian Female Healthcare Professionals: A Cross-Sectional Study - Alnazly EK; Allari R; Alshareef BE; Abu Al-khair F (Dove Medical Press, 2023)
Eman Khamis Alnazly,1 Rabia Allari,1 Basma Eid Alshareef,2 Feda Abu Al-khair2 1Department of Primary Care Nursing, Al-Ahliyya Amman University, Amman, Jordan; 2Psychology Department, Al-Ahliyya Amman University, Amman, JordanCorrespondence: Eman Khamis Alnazly, Department of Primary Care Nursing, Al-Ahliyya Amman University, Amman, Jordan, Email emanalnazly@hotmail.comPurpose: To identify the role overload, mental health distress, and quality of life among Jordanian female healthcare professionals and explore their interrelationships.Patients and Methods: This cross-sectional correlational research involved 412 female participants (physicians, nurses, and pharmacists) from the government and private sectors in Jordan. The Role Overload, Depression, Anxiety, and Stress Scale-21 (DASS-21) and the World Health Organization Quality of Life-Brief Version were used for data collection. Statistical analyses included descriptive statistics, Pearson correlation, multiple linear regression, multivariate analysis of variance, Tukey's post hoc test, Spearman rho, and linear regression tests (p=0.05).Results: Results indicate that 83.2% of participants experienced moderate to high role overload, with 72.9% displaying signs of moderate to extreme depression. Professionals working > 40 hours/week experienced elevated stress levels, while those with chronic illnesses exhibited higher mean scores for depressive symptoms (M= 16.91 vs M= 14.49, p=0.002) and stress (M= 20.55 vs M= 18.57, p=0.033). Professionals attending older individuals reported increased role overload (M= 3.66 vs M= 3.14, p< 0.001), higher stress (M=19.99 vs M=18.14, p=0.027), and lower physical (M=51.79 vs 55.41, p =0.025) and psychological (M=50.04 vs M=53.57, p=0.045) quality of life. Simple regression analysis revealed that role overload significantly predicted stress, depression, and anxiety. Role overload's impact on depression scores (β = 2.108, t=5.234, p< 0.001), as well as anxiety (β =1.933, t=5.014, p< 0.001), was associated with an inverse correlation with both physical (β =1.671, R2= 3.4, p< 0.001) and psychological (β =1.914, R2= 1.4%, p=0.018) quality of life of healthcare professionals. Mental distress and role overload significantly predicted participants' physical and psychological quality of life.Conclusion: This study established a significant association between role overload, quality of life, and psychological health of female healthcare professionals in Jordan, with implications for enhancing their well-being.Keywords: anxiety, depression, stress, quality of life, medics